If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 86 = 3x + 5x + -2 Reorder the terms: 86 = -2 + 3x + 5x Combine like terms: 3x + 5x = 8x 86 = -2 + 8x Solving 86 = -2 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 86 + -8x = -2 + 8x + -8x Combine like terms: 8x + -8x = 0 86 + -8x = -2 + 0 86 + -8x = -2 Add '-86' to each side of the equation. 86 + -86 + -8x = -2 + -86 Combine like terms: 86 + -86 = 0 0 + -8x = -2 + -86 -8x = -2 + -86 Combine like terms: -2 + -86 = -88 -8x = -88 Divide each side by '-8'. x = 11 Simplifying x = 11
| 6(8y-5)=72 | | 2m+6+5m+10=23 | | solvex^4+9x-7=0forx | | 8=2x-x+1 | | 10x^2+12-16=0 | | 5m-5+2m=2 | | 3x-8(-3-5x)=24 | | 3+x-2x=6 | | m^2=-23m-132 | | x+5(2*4x)-3=14 | | -6+6x+7x=-162 | | 6(2x-4+2x-4)=72 | | m^2=5m+66 | | x^2+25x-500=0 | | 3r+4r-7=41 | | 3x+1+x=-7 | | 48-(-23)= | | 8d-6d+3=8 | | 1.1=x+(1+x) | | 2c+3+4d-c+d= | | 6x^2=55x | | X^2+y^2-7=0 | | 5c+4d-c+d= | | 10+7x=-74 | | e^5x+7=10 | | Y+4+y-6=66 | | 5.7+77=8.2+12 | | 2(2x-1)=22 | | y=0.04t | | X^2+kx=28 | | 8=2x+7 | | f+(1/2f)=15 |